2023
DOI: 10.3390/ijerph20126117
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Diagnostic Performance of Hemoglobin in the Diagnosis of Iron Deficiency Anemia in High-Altitude Populations: A Scoping Review

Abstract: We evaluated the available literature on the diagnostic performance of hemoglobin (Hb) in the diagnosis of iron deficiency anemia (IDA) in high-altitude populations. We searched PubMed, Web of Science, Scopus, Embase, Medline by Ovid, the Cochrane Library, and LILCAS until 3 May 2022. We included studies that evaluated the diagnostic performance (sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), receiver operating characteristic (ROC) curves, and accuracy) of Hb (with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…There have been suggestions that other biomarkers, such as hepcidin [51] and hemojuvelin [52], might improve the assessment of iron deficiency and responsive anemia, although this has not been borne out of trials using a targeted approach to supplementation with hepcidin [53]. Other studies have also suggested doing away with altitude adjustment [54] for anemia, but consensus in this aspect is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…There have been suggestions that other biomarkers, such as hepcidin [51] and hemojuvelin [52], might improve the assessment of iron deficiency and responsive anemia, although this has not been borne out of trials using a targeted approach to supplementation with hepcidin [53]. Other studies have also suggested doing away with altitude adjustment [54] for anemia, but consensus in this aspect is lacking.…”
Section: Discussionmentioning
confidence: 99%